3D broadband seismic inversion: Case study of exploration cretaceous sandstone, North Arafura Basin. Issue 1 (July 2020) - Sofyadi, A; Haris, A; Riyanto, A; Sutha, I M
Abstract: This paper presents applications of Absolute and Relative Acoustic Impedance of seismic inversion for qualitative and quantitative seismic interpretation from 3D Broadband PSDM Post-stack Seismic data. A case study from the exploration area of Late Cretaceous – Early Cretaceous Clastics in Arafura Sea, eastern Indonesia has been perform in this work, where inside the study area have no well information for seismic inversion at all. The present work shows the promising contribution of applying 3D Broadband Seismic Velocity for background trend of 3D Post-Stack Model Based Seismic Inversion and perform interpretation from 3D Broadband Relative Acoustic Impedance to reduce the uncertainty associated with the seismic interpretation, to recognize the porous sand section (as an indication of hydrocarbon reservoirs) and to understand the distribution of the reservoir based on seismic data-driven, to later for define the high certainty location of exploration well.